2014
DOI: 10.1038/cmi.2014.107
|View full text |Cite
|
Sign up to set email alerts
|

A MyD88–JAK1–STAT1 complex directly induces SOCS-1 expression in macrophages infected with Group A Streptococcus

Abstract: Some pathogens can use host suppressor of cytokine signaling 1 (SOCS-1), an important negative-feedback molecule, as the main mode of immune evasion. Here we found that group A Streptococcus (GAS) is capable of inducing SOCS-1 expression in RAW264.7 and BMDM macrophages. IFN-b plays a role in GAS-induced SOCS-1 expression in macrophages following the induction of cytokine expression by GAS, representing the classical pathway of SOCS-1 expression. However, GAS also induced STAT1 activation and SOCS-1 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 47 publications
(66 reference statements)
1
23
0
1
Order By: Relevance
“…To further test this notion we performed additional assessment of SOCS1 , a key negative regulator of IFNγ signaling that is responsive to IFNs and other immune signaling pathways [31, 32]. SOCS1 responds to IFNγ in HeLa cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further test this notion we performed additional assessment of SOCS1 , a key negative regulator of IFNγ signaling that is responsive to IFNs and other immune signaling pathways [31, 32]. SOCS1 responds to IFNγ in HeLa cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A group of intracellular immune regulators, the suppressor of cytokine signaling (Socs) protein family, has been shown to negatively regulate TLR signaling via the modulation of signal transducer and activator of transcription (STAT) pathway. 12 , 13 There are eight members in the Socs family: Socs1 to Socs7 and cytokine-inducible Src homology 2 (SH2)-containing protein (Cis). Structurally, they all have a central SH2 domain and a C-terminal conserved domain termed the Socs box.…”
mentioning
confidence: 99%
“…SOCS-1 is a pleiotropic inhibitor of both the innate and adaptive immune response by controlling the actions of transcription factors and signaling effectors downstream of cytokine receptors, growth factors, and PRRs. We and others have shown that SOCS-1 inhibits MyD88 expression and actions (Serezani et al, 2011;Wu et al, 2015;Zahoor et al, 2020). SOCS-1 can prevent the differentiation of "pro-inflammatory" or M1 macrophages by limiting NF-κB p65 activation and STAT-1 actions (Duncan et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, given the role of TLRs and inflammatory cytokines in in vivo host defense, it is anticipated that endogenous SOCS-1 might help prevent tissue damage and, consequently, impacts phagocyte antimicrobial effector function. Indeed, infections with both gram-positive (Mancuso et al, 2007;Wu et al, 2015), gram-negative (Decker et al, 2005) bacteria as well as Mycobacterium tuberculosis (Manca et al, 2005) and parasites, such as Leishmania major (Bullen et al, 2003) and the fungus Candida albicans (Shi et al, 2018) promote SOCS-1 expression to actively suppress the immune response, allowing pathogen replication and immune evasion. Expression of SOCS-1 during infection correlates with reduced levels of the pro-inflammatory cytokines IL-1β, TNF-α, and IL-6 as well as antimicrobial NO and reactive oxygen species (ROS) (Duncan et al, 2017;Yoshimura et al, 2007).…”
Section: Discussionmentioning
confidence: 99%